Defining Human Factor and Ergonomic and its related issues in Malaysia Pineapple Plantations - Nur Fazrina, Mohamad Salleh; Ezrin Hani, Sukadarin (EDP Sciences, 2018)
Human factor and ergonomic has been a standardized as synonymous for a long time and has great potential to contribute in designing all kinds of systems with people. However, some opinions draw precisely distinctions among these terms. Numerous studies have been conducted in their attempt to understand the concept of human factor and ergonomic. The meaning of each term must be clearly understood before using them in any research to understand how human beings interact with surroundings. So, this paper seeks to review the definition of human factor and ergonomic. English articles and books dated as far 1970 were compiled from Taylor and Francis Online, Google Scholar and Science Direct. The keywords used in the selection of the articles are human factors, human factors engineering, ergonomics, industrial ergonomics, reviews, definition, difference and risk factors. A risk model related to each term is also provided to have more understanding towards it. Based on the finding of the literature review of human factor and ergonomic issue in pineapple plantation were explore and are categorized accordingly.